THE ROLE OF MOVIES AND TV SERIES IN IMPROVING LISTENING AND VOCABULARY SKILLS - Odilova Zuhrakhon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This research investigates the role of movies and TV series in enhancing vocabulary acquisition and listening skills through the lens of cognitive load theory. The paper analyzes the efficacy of subtitle usage in the retention of idiomatic expressions. Findings emphasize that audio-visual integration significantly improves long-term memory recall and phonological loop development in foreign language acquisition. By examining the intersection of entertainment and education, this study highlights how cinematography serves as a "multi-modal" bridge for L2 learners.